Pharmacokinetics and pharmacodynamics of isopropoxy benzene guanidine against Clostridium perfringens in an intestinal infection model - Lu, Yixing; Yang, Liuye; Zhang, Wanying; Li, Jie; Peng, Xianfeng; Qin, Zonghua; Zeng, Zhenling; Zeng, Dongping (Frontiers in Veterinary Science, 2022)
Necrotic enteritis is an intestinal disease caused by Clostridium perfringens (C. perfringens), causing high economic losses to the poultry industry. This study aimed to evaluate the antibacterial activity of isopropoxy benzene guanidine (IBG) against C. perfringens based on pharmacokinetics/pharmacodynamics (PK/PD) modeling in broilers. The PK parameters of IBG in the ileum of infected broilers following oral administration at 2, 30, and 60 mg/kg body weight were investigated. In vivo PD studies were conducted over oral administration ranging from 2 to 60 mg/kg and repeated every 12 h for 3 days. The inhibitory effect of the Imax model was used for PK/PD modeling. Results showed that the MIC of IBG against C. perfringens was 0.5–32 mg/L. After oral administration of IBG, the peak concentration (Cmax), maximum concentration time (Tmax), and area under the concentration-time curve (AUC) in ileal content of broilers were 10.97–1036.64 mg/L, 2.39–4.27 h, and 38.31–4266.77 mg·h/L, respectively. The AUC0-24h/MIC index was used to evaluate the relationship between PK and PD, and the correlation was >0.9542. After integrating the in vivo PK and PD data the AUC0-24h/MIC values needed for bacteriostatic, bactericidal, and bacterial eradication were 4.00, 240.74, and 476.98 h, respectively. For dosage calculation, a dosage regimen of 12.98 mg/kg repeated every 12 h for 3 days was be therapeutically effective in broilers against C. perfringens with MIC ≤2 mg/L. In addition, IBG displayed potent activity against C. perfringens, which is likely responsible for the disruption of the cell membrane. These results can facilitate the evaluation of the use of IBG in the treatment of intestinal diseases in broilers caused by C. perfringens.